Transactive Energy in an Urban Environment: A Case Study of Local Generation and Flexibility Potentials in a Singaporean Urban District - Zhang, Kai; Troitzsch, Sebastian; Zhang, Si-Yue; Teh, Erine Siew Pheng; Subramanian, Lalitha; Massier, Tobias (Frontiers in Energy Research, 2021)
This paper presents a case study of distributed generation and flexibility potential for a multi-energy system in an urban district in Singapore. The analysis incorporates real-life data of a local energy system consisting of flexible loads (i.e. district cooling demand from air-conditioned buildings), and distributed generators (DGs) (i.e. waste-to-energy (W2E) generators, photovoltaic (PV) generators) from a representative study area. The demand-side flexibility (DSF) potentials from air-conditioned buildings are derived based on a state-space model and its underlying base-load estimation. Besides the conventional consideration of PV system integration in the urban environment, we conduct a feasibility study of the distributed W2E technology deployment and estimated the generation potentials for the study area. Furthermore, to facilitate the flexibility and energy exchange, market frameworks are proposed to harvest the energy and flexibility from distributed energy resources (DERs) and in the real-time market context in Singapore.